1986
DOI: 10.1104/pp.81.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Primary Structure of a Proline-Rich Zein and Its cDNA

Abstract: Eighty-five cDNA clones for 'y-zein (proline-rich zein) from a cDNA expression library were isolated using specific antibody and cDNA probes. Nucleotide sequences of seven independent clones were determined and found to be identical in regions where they overlapped. The primary structure of the mature protein, determined from the sequence of one near full-length clone, consists of 204 amino acids. It has a molecular weight of 21,824 daltons, about 5 kilodaltons less than that estimated by sodium dodecyl sulfat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 19 publications
1
31
0
1
Order By: Relevance
“…However there was no pronounced effect of ionic strength on the particle size of zein nanoparticles. Zein has relatively a lesser proportion of charged amino acids compared other proteins such as albumin (9). The results suggest that the zein nanoparticles are sterically stabilized (25) by the surfactants and therefore the electrostatic interactions may not play a predominant role.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…However there was no pronounced effect of ionic strength on the particle size of zein nanoparticles. Zein has relatively a lesser proportion of charged amino acids compared other proteins such as albumin (9). The results suggest that the zein nanoparticles are sterically stabilized (25) by the surfactants and therefore the electrostatic interactions may not play a predominant role.…”
Section: Discussionmentioning
confidence: 71%
“…It consists of three fractions that vary in molecular weight (MW) and solubility (9). These include α-zein (MW, 19-24 kDa; 75-80% of total protein), β-zein (17-18 kDa, 10-15%), and γ-zein (27 kDa, 5-10%) (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several genes have been shown to be expressed in an inducible, tissue-specific or developmentally controlled manner in transgenic plants (8,24,26,35). Promoters have been dissected into various expression signals by using this approach (8,9,24); however, there are many levels of control that remain undefined (3,31,43). For example, position effects have been observed in which the same construct gives considerable variation in expression levels between individual transformants (8,24,35).…”
mentioning
confidence: 99%
“…The coding region of this gene contains 671 bp and no introns are found in the coding region. Wang and Esen ( 1986) reported that the y-zein contains 204 amino acid residues. The predicted molecular weight of this protein is about 27-kD.…”
Section: Genetics and Primary Structure Of Zeinsmentioning
confidence: 99%